Solvent-Free Preparation of N,N′-Dialkylbenzenediamines - Kuo, Hsin-Ya; Liao, Bei-Sih; Liu, Shiuh-Tzung (Synthesis, 2013)
A diiridium complex, stabilized by a bis(N-heterocyclic carbene) ligand, was found to be an effective precatalyst for the N,N′-dialkylation of o-, m-, and p-benzenediamine in excellent yields. Benzyl and primary aliphatic alcohols were used as alkylating reagents. Furthermore, the reactions were carried out without using any organic solvent, offering an environmentally benign process.
Keywords: alkylation; amination; iridium; catalysis; carbene complex